Adaptive Immune Response Signaling Is Suppressed in Ly6Chigh Monocyte but Upregulated in Monocyte Subsets of ApoE-/- Mice — Functional Implication in Atherosclerosis - Yang, Pingping; Wu, Qinghua; Sun, Lizhe; Fang, Pu; Liu, Lu; Ji, Yong; Park, Joon-Young; Qin, Xuebin; Yang, Xiaofeng; Wang, Hong (Frontiers in Immunology, 2021)
Rationale: Inflammatory monocyte (MC) subset differentiation is a major feature in tissue inflammatory and atherosclerosis. The underlying molecular mechanism remains unclear. Objective: This study aims to explore molecule targets and signaling which determinate immunological features in MC subsets. Methods and Results: Blood Ly6Chigh and Ly6Clow MC subsets from control and ApoE-/- mice were isolated by flow cytometry sorting and subjected for bulk high-throughput RNA-sequencing. Intensive bioinformatic studies were performed by analyzing transcriptome through four pairs of comparisons. A total of 80 canonical pathways and 16 enriched pathways were recognized by top-down analysis using IPA and GSEA software, and further used for overlapping analysis. Immunological features and signaling were assessed on four selected functional groups, including MHCII, immune checkpoint, cytokine, and transcription factor (TF). Among the total 14578 significantly differentially expressed (SDE) genes identified though above four comparison, 1051 TF and 348 immunological genes were discovered. SDE immunological genes were matched with corresponding upstream SDE TF by IPA upstream analysis. Based on an intensive literature search, we found that the identified SDE immune checkpoint genes in Ly6Chigh MC are associated with pro-inflammatory/atherogenic balance function. Immune checkpoint genes GITR, TIM1, CTLA4, and CD96 were upregulated in Ly6Clow MC from all mice and presented anti-inflammatory/atherogenic features. Six cytokine genes were upregulated in Ly6Chigh MC from all mice and associated with pro-inflammatory/atherogenic feature. Cytokine receptor gene Il12rb2, Il1r1, Il27ra, Il5ra, Ngfr, Ccr7, and Cxcr5 were upregulated in Ly6Clow MC from all mice and presented anti-inflammatory/atherogenic features. MHCII genes were elevated in Ly6Clow MC from all mice. ApoE-/- augmented pro-atherogenic/inflammatory and antigen-presenting cells (APC) feature in both subsets due to elevated expression of cytokine genes and MHCII gene (H2-Aa and H2-Ea-ps). Finally, we modeled immunological gene expression changes and functional implications in MC differentiation and adaptive immune response for MC subsets from CT and ApoE-/- mice. Conclusions: Ly6Chigh MC presented pro-inflammatory/atherogenic features and lower APC potential. Ly6Clow MC displayed anti-inflammatory/atherogenic features and higher APC potential. ApoE-/- confers upon both subsets with augmented pro-atherogenic/inflammatory function and APC potential.